PRINCIPLES FOR THE FORMATION OF LEXICAL COMPETENCE IN THE TEACHING OF INDUSTRIAL TERMS OF THE ENGLISH LANGUAGE (On the example of ICT terms) - Saidqosimova Azizakhon Saidmavlonovna (Bright Mind Publishing, 2025)
This article explores the fundamental principles for developing lexical competence in teaching industrial English terminology, with a particular focus on Information and Communication Technology (ICT) terms. It emphasizes the importance of contextualized learning, thematic grouping, integration of language skills, use of authentic materials, active practice, multimodal support, repetition, and understanding of word formation. The study addresses challenges faced by learners and educators in mastering specialized vocabulary in a rapidly evolving technical field. The proposed principles aim to enhance learners' ability to effectively comprehend and use ICT terms, thereby improving their professional communication in the global industrial environment.
Keywords: Lexical competence, industrial English, ICT terminology, vocabulary teaching, technical English, contextual learning, specialized vocabulary, language skills integration.